HOPE OF WOMEN UNDERGOING CHEMOTHERAPY TREATMENT FOR BREAST CANCER - Eduardo Tavares Gomes; Simone Maria Muniz da Silva Bezerra (Cogitare Enfermagem, 2019)
Objective: To analyze the levels of hope of women undergoing chemotherapy treatment and related factors. Method: Observational, cross-sectional, quantitative study conducted in a chemotherapy service of a teaching hospital in northeastern Brazil from March to September 2018. For this study, 55 women undergoing chemotherapy for breast cancer were interviewed. The Spiritual Well-Being Scale, the Herth Hope Index and the Duke Religion Index were applied. Results: Religiousness and spiritual well-being were significant predictors of hope (p = 0.024), but the small magnitude of the effect had a low predictive value (f²=0.29), explaining 22.6% (R²) of the variable’s behavior. Spiritual well-being was the only independent predictor variable for hope (β = 0.439; t = 3.376; p = 0.001). Conclusion: The main predictor variable of hope was spiritual well-being. Hope was found to be independent of sociodemographic factors and treatment.